Harga dan Lokasi terhadap Keputusan Pembelian di Perumahan Griya Alam Nusantara Tipe 36/72 - Moh. Heriski Ramadan; Erni Yuningsih; Endang Silaningsih (Journal of Management and Bussines (JOMB), 2024)
This research aims to identify the impact of marketing variables (price and location) on consumer purchasing decisions. The research method used was non-probability sampling using a questionnaire as an instrument to collect data from 163 respondents. The research results show that simultaneously, price and location have a positive and significant effect on purchasing decisions, with an R Square value of 59.8%. The remaining 40.2% was influenced by other factors not examined in this study. Partially, price and location also have a significant influence on purchasing decisions. The research results show that the location variable has a greater influence than the price variable on purchasing decisions in Griya Alam Nusantara Type 36/72 housing. The conclusion is that in the context of Griya Alam Nusantara Type 36/72 housing, both price and location are crucial factors that need to be considered in determining consumer purchasing decisions. Keywords: Price, Purchase Decision, Location